2020
DOI: 10.1158/1538-7445.sabcs19-p2-13-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-13-03: Lifestyle changes after breast cancer: A prospective study among 8580 women

Abstract: Background: Persistence of unhealthy behaviors may adversely affect breast cancer (BC) outcomes and quality of life. Cancer diagnosis can represent a teachable moment and a powerful catalyst to correct such behaviors. It has been suggested that some cancer patients (pts) may be motivated towards a healthier lifestyle, particularly in case of a worse cancer-related prognosis. In this study we aimed at understanding the evolution and barriers in adoption of health behaviors after BC. Methods: We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some authors also suggested that receiving a diagnosis of more advanced BC, needing more intense chemotherapy treatment, may lead patients to adopt behaviors that they believe can improve their clinical condition and prognosis. For example, in CANTO we previously observed that receiving chemotherapy was associated with higher odds of smoke cessation and adjuvant endocrine therapy persistence, supporting the notion that risk perception related to BC prognosis may somehow drive certain behaviors after diagnosis [51,52]. Furthermore, some authors expressed concerns that there may be decreased initiation of clinically indicated chemotherapy among patients using OCAM, as refusal is correlated to an increased risk of death [53,54].…”
Section: Discussionmentioning
confidence: 66%
“…Some authors also suggested that receiving a diagnosis of more advanced BC, needing more intense chemotherapy treatment, may lead patients to adopt behaviors that they believe can improve their clinical condition and prognosis. For example, in CANTO we previously observed that receiving chemotherapy was associated with higher odds of smoke cessation and adjuvant endocrine therapy persistence, supporting the notion that risk perception related to BC prognosis may somehow drive certain behaviors after diagnosis [51,52]. Furthermore, some authors expressed concerns that there may be decreased initiation of clinically indicated chemotherapy among patients using OCAM, as refusal is correlated to an increased risk of death [53,54].…”
Section: Discussionmentioning
confidence: 66%